Storytelling for lawyers - Meyer, Philip N. (Oxford University Press, 2014)
Good lawyers have an ability to tell stories. Whether they are arguing a murder case or a complex financial securities case, they can capably explain a chain of events to judges and juries so that they understand them. The best lawyers are also able to construct narratives that have an emotional impact on their intended audiences.